Diabetic macular edema: a literature review - Risso, Wellington Fernando; Pinheiro, Matheus Roque; Pereira, Leonardo Amarante; Abucham-Neto, Júlio Zaki; Veiga, Glaucia Luciano da; Fonseca, Fernando Luiz Affonso; Lima, Vagner Loduca (ABCS Health Sciences, 2020)
Diabetic Macular Edema is a major cause of visual impairment in economically active population, being responsible for a significant impact in quality of life in the affected population, as well as high costs to the health care system. Over decades, some studies have compared treatments using Laser, Anti-VEGF and intravitreous corticosteroids, establishing protocols to reach effectives therapies. Thus, it is essential an entire understanding of available therapies to reach the goal of disease control, in an individual basis and in a collective health care system, as efficient as possible.